Applying Climate Information for Supporting Farming System of Food Crop - ELZA SURMAINI; RIZALDI BOER; H. SIREGAR (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2006)
The events of climate extreme that increase the crop yield uncertainty causing financial loss of farmers. To ensure economic profitability, farmers need to tailor their cropping pattern to the climate forecast. The study was conducted in Ciparay and Bojongsoang sub-District, the central crop production of Bandung District from March to August 2005. Research aimed to analyze climate information value based on farming system strategy for accruing farmer income. Farming system in climate extremeevents was determined by maximizing expected utility of wealth. Farming system in two sub-District was assessed by Rapid Rural Appraisal. Climate information value was the difference between income with conventional farming and income using farming system strategy. Result of the survey indicated that dominant cropping pattern in the study area was rice-rice-fallow. The second rice was vulnerable to drought particularly in extremeyears. Further analysis suggested that extreme climate events were mostly associated with ENSO (El-Niño Southern Oscillation) events. From farming system simulation model, it was found that in El-Niño years, to maximize income, farmers should planted all farm with maize. Planting non-rice crops can be done after April (early May), to get maximist income, they should plant all farm with soybean. Risk averter farmers might diversify their crops, i.e. by fallowing part of their lands and planting the remaining lands with maize and soybean. The use of climate information in El-Niño years will give higher economic benefit to farmers than in La-Niña years. The difference in economic benefit was determined by the proportion of land allocated for rice and nonrice crops. In El-Niño years, farmers who plant all their lands for second planting with rice crop will get loss due to significant decrease in rice yield, while those who plant part or all of their land with non-rice crops will gain benefit as they will get yield. Therefore, farmers who are willing to take risks by planting part or all of their land with non-rice crops in years which were forecasted to be El-Niño years will get higher income than farmers who are not willing to change their rice crops.